(3ChQGO hCOYjI aj QeVGfs
(3ChdgG (B:s
(3Gddge Ef gPG TgQ QeVGf GdPi CfRd ajg GdbQBf Qhi CHh HUjQ Yf CHj YHO Gddg Ydjg GdSGe bGd Jbhd ai cd djdI ef TgQ QeVGf s
(3BNQgG (B:s
(3hGcTa cQhHfG hGZKfG hGLQfG hGQMefG jG CQMe GdQGMejf hGdMeO ddg QH GdYGdejf Je hced s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs